Agro-economic evaluation of oilseed crops in rice fallow situation in Alfisols: AGRO-ECONOMIC EVALUATION OF OILSEED CROPS IN RICE FALLOW SITUATION IN ALFISOLS - A V RAMANJANEYULU; K INDUDHAR REDDY; M V NAGESH KUMAR; M VENKATA RAMANA; G SURESH (Journal of Oilseeds Research, 2020)
A field study was conducted with an objective of identifying suitable and profitable oilseed crop(s) for rice fallow situation in Alfisols. Four crops viz., castor, groundnut, sunflower and sesame were evaluated for two years (rabi/summer 2014-15 and 2015-16).The castor equivalent yield was significantly higher with groundnut (3978 and 3864 kg/ha) and was followed by sesame crop (3460 and 3306 kg/ha). The pooled analysis revealed that groundnut and castor recorded significantly higher production efficiency, but, significantly higher WUE was registered with groundnut and sesame. Higher gross returns (` 73,687/ha)were accrued with groundnut, whereas, higher net returns (` 33,441/ha) and B:C ratio (2.56) were accrued when sesame was grown in rice fallows. Hence, sesame has been identified as the most profitable crops in rice fallows under South Indian conditions in Alfisols.